2004
DOI: 10.1142/s0219477504001653
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization Approach to Analysis of Biological Systems

Abstract: In this article we review the application of the synchronization theory to the analysis of multivariate biological signals. We address the problem of phase estimation from data and detection and quantification of weak interaction, as well as quantification of the direction of coupling. We discuss the potentials as well as limitations and misinterpretations of the approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 47 publications
(63 reference statements)
0
45
0
Order By: Relevance
“…design is often used to improve the throughput, where a number of parallel channels with different cross-sectional dimensions are connected to a single inlet. [15][16][17][18] The FSS generated within individual channels varies due to different fluidic resistances of these channels. Such devices are especially useful for studying the magnitude-dependent cell response upon FSS.…”
Section: Introductionmentioning
confidence: 99%
“…design is often used to improve the throughput, where a number of parallel channels with different cross-sectional dimensions are connected to a single inlet. [15][16][17][18] The FSS generated within individual channels varies due to different fluidic resistances of these channels. Such devices are especially useful for studying the magnitude-dependent cell response upon FSS.…”
Section: Introductionmentioning
confidence: 99%
“…To be mentioned here are the effects of noise-induced order in chaotic dynamics (Matsumoto and Tsuda, 1983), synchronization of self-sustained oscillators (Pikovsky et al, 2000), cumulative effects of many different scales (Aurell et al, 1996), coherence resonance (Pikovsky and Kurths, 1997), stochastic resonance (Nicolis and Nicolis, 1981;Benzi et al, 1981), and interference between initial error and stochastic forcing (Seki et al, 1993). These effects in some respects are close and cannot be easily distinguished from one another when signals reflect different variables of the same system (Rosenblum et al, 2004).…”
Section: Physical Mechanisms Of Perturbation Growthmentioning
confidence: 99%
“…The nature of the couplings has been extensively studied from measured data in recent years [4][5][6][7][8][9][10][11][12][13]. Recently, Schäfer et al [14,15] and Rosenblum et al [16] found that there were sufficiently long periods of hidden synchronization and concluded that the cardiorespiratory synchronization and respiratory sinus arrhythmia (RSA) are two competing factors in cardiorespiratory interactions.…”
Section: Introductionmentioning
confidence: 99%